Process of ammonia removal from anaerobic digestion and associated ammonium sulphate production: Pilot plant demonstration. (1st April 2020) - Costamagna, P.; Giordano, A.; Lazzarini, Y.; Delucchi, M.; Busca, G.
Abstract: A process for the continuous extraction of ammonia from anaerobic digesters is proposed. In this process, a portion of the sludge treated in the digesters is continuously withdrawn and transferred to a thin film evaporator (TFE) unit, where the ammonia is stripped through a biogas stream. The ammonia-rich biogas is treated with a sulfuric acid/water solution in a reactive absorption unit, with production of ammonium sulphate. The chemistry of a CH4 /CO2 /NH3 gas phase in thermodynamic equilibrium with a liquid sulfuric acid/water solution is investigated theoretically, with focus on the simultaneous absorption of CO2 and NH3 into the liquid phase. Pilot plant experimental data confirm the theoretical results. Further pilot plant experimental results obtained during on-off cycles of the stripping equipment demonstrate that, when the TFE unit is off, ammonia concentration in the digestate rises quickly, while, when the stripping equipment is turned on again, ammonia concentration drops down. On average, during the 180 days of pilot plant experimentation, 4.1 g N–NH4 per kg of sludge fed to the digester, i.e. 19.3 g N–NH4 per kg of total solids (TS) fed to the digester, are stripped from digestate and recovered as ammonium sulphate, demonstrating the feasibility of the proposed concept. Highlights: A process for stripping ammonia from an anaerobic digester is proposed. Stripping is carried out through biogas. Upon absorption into a water/sulfuric acid stream, ammonium sulphate is formed. Pilot plant experimental data confirm theoretical calculations. TAN in the digester decreases when the side-stream ammonia stripper is in operation.